Urinary MicroRNAs, Possible Biomarkers for Early Detection of Patients with Autosomal Dominant Polycystic Kidney Disease (ADPKD) (Iranian Journal of Kidney Diseases, 2023)
Introduction. Autosomal dominant polycystic kidney disease (ADPKD) is a prevalent renal disorder that causes abnormal growth of renal epithelial cells. The excessive expansion of renal epithelial cells can lead to cyst formation that is associated with serious renal complications. The early diagnosis of ADPKD makes the control of the disease somehow attainable. Regarding the diagnostic potential of microRNAs (miRs) as robust clinical biomarkers, the present study aimed to examine the potential of urinary miRs in early diagnosis of ADPKD in asymptomatic patients. Methods. Urine samples were obtained from 20 asymptomatic ADPKD patients and 20 healthy control individuals and the miR content of the samples was extracted and converted to cDNA for the qRT-PCR experiment. The relative expressions of miR-17, miR-21, miR-143, and miR-223 were evaluated in ADPKD cases and healthy individuals. Serum levels of kidney function markers were also evaluated in the study participants. Results. The urine samples of patients with ADPKD demonstrated higher levels of miR-17, miR-21, and miR-143 along with a lower miR-223 level compared to the healthy control group. Conclusion. This study revealed the differential expression of the studied miRs in ADPKD patients. Detection of miRs in urinary samples might provide a useful platform for early diagnosis of ADPKD in asymptomatic patients.  DOI: 10.52547/ijkd.7281